Sull'attualità del dispositivo della razza. - Simona Miceli (Cambio)
The article proposes a re-reading of W.E.B. Du Bois' The Souls of the Black Folk, focusing on his conceptual contribution to the sociological analysis of the category of “race”. After a brief outline of the intellectual history of this scholar, who for a long time has not been adequately recognised as one of the founders of American sociology, a brief overview of the text under review is offered. It highlights the innovative elements through which Du Bois was able to narrate and analyse the process of transition from slavery to the emancipation of the African American people. The two main analytical concepts developed in the volume are the colour line and double consciousness, to which this contribution pays particular attention to highlight their ability to focus on the processes of social construction of race, in both structural and subjective terms. Finally, we dwell on the relevance of Duboisian thought and the effectiveness of his interpretative perspective to read in a complex and transversal way various phenomena that cross contemporary societies, and specifically Italy, where the social category of race is not always sufficiently taken into consideration.